Privacy Amplification of QKD Protocol in a Quantum Router - S. Chaiyasoonthorn; P. Youplao; S. Mitatha; P.P. Yupapin (My University, 2012)
We propose a new system of quantum cryptography for QKD protocol with privacy amplification for internet security using Gaussian pulse propagating within a nonlinear ring resonator system, quantum processor and a wavelength router. To increase the channel capacity and security, the multiplexer is operated incorporating a quantum processing unit via an optical multiplexer. The transmission part can be used to generate the high capacity quantum codes within the series of micro ring resonators and an add/drop filter. The receiver part can be communicated by using the quantum key (quantum bit, qubit) via a wavelength router and quantum processors. The reference states can be recognized by using the cloning unit, which is operated by the add/drop filter, where the communication between Alice and Bob can be performed. Results obtained have shown that the correlated photons can be generated and formed the entangled photon pair, which is allowed to form the secret key between Alice and Bob. In application, the embedded system within the computer processing unit is available for quantum computer.
Keywords: Quantum key distribution; Quantum Information and Cryptography